Arachidonic acid-induced platelet aggregation and acetylsalicylic acid treatment during pregnancy in women with recurrent miscarriage, a post hoc study. (17th February 2022) - Blomqvist, Lennart R. F.; Strandell, Annika M.; Jeppsson, Anders; Hellgren, Margareta S. E.
Abstract: In this post hoc study, arachidonic acid (AA)-induced platelet aggregation during pregnancy with and without acetylsalicylic acid (ASA) treatment was studied in 323 women with unexplained recurrent first-trimester miscarriage and in 59 healthy women with normal pregnancies. All women had normal AA-induced platelet aggregation in the non-pregnant state. Women with recurrent miscarriage were treated with 75 mg ASA or placebo daily. AA-induced platelet aggregation was measured with multiple electrode impedance aggregometry and presented in units (U), where 1 U = 10 aggregation units x minutes. There were no significant differences in platelet aggregation between placebo-treated women with recurrent miscarriage and healthy women. The mean differences were -0.7 (95%CI; −7.0; 5.6) U in the non-pregnant state, 3.8 (95%CI; −4.6; 12.2) U during the late first trimester and 1.7 (95%CI; −6.7; 10.3) U and 4.1 (95%CI; −3.9; 12.0) U during the early and late third trimester, respectively. ASA reduced platelet aggregation by median −84.0% (Q1; Q3; −89.8; −76.3), −79.9% (−84.7; −69.2) and −75.7% (−83.5; −49.5), respectively, during pregnancy. The degree of inhibition by ASA decreased during the third trimester ( p < .0001). There were two (1.9%) complete non-responders to ASA and 32.1% with a partial response. The rate of subsequent miscarriage was not affected by ASA, which did not seem to influence the rate of early miscarriage if treatment was initiated when a viable pregnancy was detectable by ultrasound.